The floor, shade and entrance to the main sanctum - Temples of India Project Team (Jio Institute, 2024)
The complex in which the present temple is situated is tightly paved with bricks whereas the mandapa in front of the main sanctum is refloored with modern tiles. The temple is covered with a metal sheet roof for shade. A set of steps lead up to the mandapa. A closer look of the steps reveals remnants of the original temple placed as decorations to the stairs. There is a small steel gate which further leads to the mandapa of the temple.